The Power of Religion / Religion and Power Third Annual Conference 2020 - Selderhuis, Herman J. (European Academy of Religion (EuARe) Lectures, 2023)
How does the powerful effect that religion has on public and personal life relate to the various spheres of our culture? Is the relationship between power and religion always negative or can religion also affect individuals and societies positively? This volume of the EuARe Lectures collects the texts delivered at the Third Annual Conference of the European Academy of Religion (2020) on the topic "The Power of Religion / Religion and Power".